INFLUENCE OF PHYTASE ENZYME ON GROWTH PERFORMANCE AND SURVIVAL RATE CHALLENGED WITH SAPROLEGNIA SPP. IN COMMON CARP - & Mustafa, Fadhal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate the effect of phytase as a feed additive on growth performance and survival rate against Saprolegnia spp.in common carp, Cyprinus carpio L. A total of 120 C. Carpio (initial mass 20.05-20.35g) were randomly stocked into six treatments in duplicate (10 fish/tank) as follows: T1, T2, and T3 were fed the basal diet supplemented with phytase at 1000, 2000, and 4000 IU/Kg diet respectively, while T4 were fed on basal diet plus β-glugan at a concentration of 8.5 g/kg as well as the control group was fed basal diet without any addition of phytase. Results showed after 60 days of feeding period, that the addition of phytase enzyme was significantly (p<0.05) affected on daily growth (DG), specific growth rate (SGR) and feed conversion ratio (FCR) in T3 and T2 followed by T4 and T1 compared to control group. At the end of the experimental period (60 days) fish were challenged with Saprolegnia spp. After 15 days of challenge test, the best survival rate was recorded in T3 (100%) followed by T2 (80%) then T1 (70%) respectively. All treatment groups were better than the positive control group which recorded 40 %. Based on these results, this study approved the potency of the phytase enzyme on growth performance and survival rate against the Saprolegniasis in common carp.